Microbial Profile and Antibiotic susceptibility pattern of infectious agents isolated from patients admitted to intensive care unit of a tertiary care center at Bihta. (Indian Journal of Public Health Research & Development, 2025)
Objectives :Patients with critical illness are admitted in intensive care units (ICU). A right antibiotics given to these patients timely, will help in their recovery. This study was done with an aim to know the profile of microorganism in the ICU setting and their antibiotic susceptibility pattern. Materials and methods :The study was conducted for 1 year period in a tertiary care hospital at Bihta, Patna. All the clinical samples received from various ICU’s were subjected to culture and sensitivity by standard microbiological procedures.Results :A total of 540 samples were received from various ICU’s. The culture positive rate in ICU was 22.8%. The most common culture positive sample received was blood 59 (48%). Among culture positive samples, 68 (55.3%) were Gram negative bacteria (GNB), followed by 43 (35%) Gram positive cocci (GPC) and 12 (9.7%) fungal isolates. Escherichia coli 28 (22.8%) was the most common isolates among GNB. Among GPC, the most common isolates was Coagulase negative Staphylococcus species (CONS) 32 (26%). All fungal isolates were Non albicans Candida (9.8%).Conclusion : This will help in making antibiotic policy of the ICU setting and will guide  cliniciansfor empirical therapy. It will prevent misuse of antibiotics and helps to combat antibiotic resistance.
Keywords: ICU, GNB, GPC, Antibiotics, Antibiotic resistance.